(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Arachnoid cysts, typically benign and congenital, are fluid-filled lesions that often go unnoticed and are discovered incidentally. Though common in the general population, their presence is rarely highlighted in forensic cases. This report focuses on a cerebellopontine arachnoid cyst (CPAC) unexpectedly found during a medico-legal autopsy. The case involved a 28-year-old male who had a history of fever, dry cough, and breathlessness. Upon external examination, no notable abnormalities were identified. Internally, the autopsy revealed multiple white nodules on the lungs and spleen, and a cystic lesion at the right cerebellopontine angle, compressing the brainstem. Histological analysis confirmed the presence of the CPAC along with significant lung inflammation and damage. The lung condition was identified as the cause of death. CPACs, though rare, pose challenges in forensic contexts because they can grow, compress critical areas of the brainstem, or even rupture, potentially leading to sudden death. While these cysts